Multi-ion co-doped BiVO4-based microwave dielectric ceramic and preparation method thereof

By co-doping BiVO4-based microwave dielectric ceramics with multiple ions, the balance problem between the dielectric constant and the resonant frequency temperature coefficient of BiVO4 microwave dielectric ceramics is solved, and low-temperature sintering and near-zero resonant frequency temperature coefficient are achieved, which is suitable for 5G/6G communication equipment.

CN120698780AInactive Publication Date: 2025-09-26SHAANXI AUSIC ELECTRONICS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202511187568.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-25
Publication Date
2025-09-26
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing BiVO4 microwave dielectric ceramics have difficulty achieving an ideal balance between the dielectric constant and the resonant frequency temperature coefficient, resulting in frequency drift and instability of the device, and the high traditional sintering temperature leads to high energy consumption.

Method used

By using multi-ion co-doped BiVO4-based microwave dielectric ceramics and controlling its phase change process by doping La3+, Nd3+, Sm3+, Eu3+ and Gd3+ ions in BiVO4, Bi1-5x(LaxNdxSmxEuxGdx)VO4 ceramics were prepared, achieving serialized dielectric constants and near-zero resonant frequency temperature coefficient.

Benefits of technology

While achieving serialization of dielectric constants, it has excellent quality factor and near-zero resonant frequency temperature coefficient, which reduces sintering temperature and energy consumption, and is suitable for the high integration requirements of 5G/6G communication equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120698780A_ABST
    Figure CN120698780A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-ion co-doped BiVO4-based microwave dielectric ceramic and a preparation method thereof, the chemical formula of the microwave dielectric ceramic is Bi < 1-5x > (LaxNd < x > Sm < x > Eu < x > Gd < x >) VO4, and x is more than or equal to 0.025 and less than or equal to 0.1. The invention designs a series of Bi1-5x (LaxNdxSmxEuxGdx) VO4 (x is more than or equal to 0.025 and less than or equal to 0.1) ceramics by selecting equivalent La < 3 + >, Nd < 3 + >, Sm < 3 + >, Eu < 3 + > and Gd < 3 + > as substitute ions of Bi < 3 + >, and aims to realize serialization of dielectric constants of microwave dielectric ceramics, and meanwhile, the microwave dielectric ceramics also have excellent quality factors, especially have near-zero temperature coefficient of resonance frequency. The microwave dielectric ceramic has excellent microwave dielectric properties, the epsilon r value of the microwave dielectric ceramic reaches 19.85-66.98, the Q * f value of the microwave dielectric ceramic reaches 7904-16240 GHz, especially when x is equal to 0.055, the microwave dielectric ceramic reaches the near-zero tau f value of + 8.42 ppm / DEG C, and the microwave dielectric ceramic has remarkable industrial application value. The sintering temperature of the microwave dielectric ceramic is far lower than that of traditional microwave dielectric ceramic, energy consumption can be greatly reduced, the production cost can be reduced, low-temperature co-firing of the dielectric ceramic and the silver electrode can be achieved, and therefore the module is miniaturized, and the requirement of 5G / 6G communication equipment for high integration level is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of dielectric ceramics, and in particular relates to a multi-ion co-doped BiVO4-based microwave dielectric ceramic and a preparation method thereof. Background Art

[0002] Microwave dielectric ceramics are a type of functional ceramic material designed specifically for the microwave (300MHz~300GHz) frequency band. Their core function is to serve as a key dielectric for passive devices such as microwave resonators, filters, oscillators, capacitors and microwave antennas, playing the role of dielectric isolation, dielectric waveguide and dielectric resonance. They are key materials for modern microwave communications such as mobile communications, satellite communications, global satellite positioning systems, Bluetooth technology and wireless local area networks. Their performance directly determines the efficiency, size and stability of modern wireless communication (5G / 6G, satellite communications, radar) systems.

[0003] The core performance indicators of microwave dielectric ceramics include dielectric constant (ε r ), quality factor (Q value) and near-zero resonant frequency temperature coefficient (τ f However, there are mutual influences and constraints between these performance indicators, such as: ε r The value determines the wavelength shortening effect of electromagnetic waves propagating in the material, ε r The higher the value, the smaller the physical size of the resonator can be made, which is the core driving force for achieving device miniaturization. However, the pursuit of high ε r The value is usually accompanied by adverse effects, which will lead to a decrease in Q value, τ f The difficulty of value control increases; however, to obtain a high Q value, it is often necessary to select ε r To achieve near-zero τ f The value often needs to be compounded by different τ f To achieve the best performance of microwave components, an ideal balance must be achieved between these performance parameters.

[0004] In addition, different application fields have different requirements for signal transmission rate and device size. Therefore, it is necessary to select suitable types of microwave dielectric ceramic materials for each application scenario and rationally design microwave dielectric ceramics with a series of performance characteristics to meet more application fields. The signal transmission rate in microwave dielectric ceramics and the size of the device are mainly determined by ε r The wavelength of electromagnetic waves transmitted in a medium and the dielectric constant have the following relationship: Where λ d and λ0 are the wavelengths of the signal in the medium and vacuum respectively. It can be seen that the wavelength of the signal transmission is related to the dielectric constant ε of the dielectric medium.r The square root is inversely proportional. The resonator size is an integer multiple of half the wavelength of the transmitted signal, which is an important condition for the formation of standing waves. Therefore, a larger dielectric constant ε r Therefore, it is very necessary to develop a series of microwave dielectric ceramics with high dielectric constant and resonant frequency temperature stability.

[0005] At present, the most studied high dielectric constant microwave dielectric ceramic systems are BaO-PbO-Nd2O3-TiO2 system (ε r ~90) [Crute J R. Microw. Opt. Technol. Lett., 2001, 31(4): 313-314], Ba 6- 3x Ln 8+2x Ti 18 O 54 (Ln = Lanthanide rare earth elements) Tungsten bronze material (ε r ~80)

Ohsato H, Kato H, Mizuta M,et al. Jpn. J. Appl. Phys., 1995, 34(9B):5413-5417

Zhou D,Pang LX, Wang DW, et al. J. Mater. Chem. C, 2018, 6(35):9290-9313

[0006] The common ways to adjust the temperature stability of the resonant frequency include solid solution, composite, stacking process and non-stoichiometric ratio, but they often face mutual limitations due to the trade-off between different parameters. Previous studies have shown that the τ fThe value is affected by various factors, including crystal structure, phase composition and the presence of dopants. At present, researchers mainly focus on ion doping to control the dielectric properties of BiVO4 ceramics. Zhou et al. prepared a series of Bi 1-x Ln x VO4 (where Ln = Ce, Nd or Y) ceramics have successfully f The value was adjusted to near zero, and they found that temperature compensation could be obtained in the two-phase region formed by single rare earth ion doping [Zhou D, Pang LX, Guo J, et al. Inorg. Chem., 2014, 53(2):1048-1055; Zhou D, Li WB, Xi HH, et al. J. Mater. Chem. C, 2015,3(11): 2582-2588]. In addition, the appropriate amount of (Fe 1 / 3 Mo 2 / 3 ) 5+ and (Fe 1 / 3 W 2 / 3 ) 5+ Composite ion doping at the V site can also achieve temperature compensation for BiVO4 [Zhou D, Pang LX, Guo J, et al. J. Mater. Chem., 2012, 22(40); Wu FF, Zhou D, Xia S, et al. J. Eur.Ceram. Soc., 2022, 42(13): 5731-5737]. These methods can replace Bi 3+ Still V 5+ , all of which demonstrate the potential of composition engineering in adjusting the microwave dielectric properties of BiVO4 ceramics. How to design the composition to achieve the resonant frequency temperature coefficient (τ f ) is close to zero and has an excellent quality factor and a relatively ideal dielectric constant, which is a topic worth exploring in this field. Summary of the Invention

[0007] In order to realize the serialization of dielectric constants of microwave dielectric ceramics while having excellent quality factor, especially near-zero resonant frequency temperature coefficient and low sintering temperature, the present invention proposes a multi-ion co-doped BiVO4-based microwave dielectric ceramic and its preparation method.

[0008] To achieve the above object, the present invention provides the following technical solutions: A multi-ion co-doped BiVO4-based microwave dielectric ceramic, the chemical formula of which is Bi 1-5x (La x Nd x Smx Eu x Gd x )VO4, where 0.025≤x≤0.1.

[0009] Preferably, x=0.055.

[0010] The preparation method of the multi-ion co-doped BiVO4-based microwave dielectric ceramic comprises the following steps: S1, the original powders of Bi2O3, La2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3 and NH4VO3 were prepared according to Bi 1-5x (La x Nd x Sm x Eu x Gd x ) Weighing and mixing the components of VO4; S2, mixing the original powders weighed in S1 and performing wet ball milling, and drying the ball mill slurry to obtain a mixture A; S3, pre-calcining the mixture A to obtain a pre-calcined powder; S4, performing a secondary wet ball milling on the pre-calcined powder obtained in S3, and drying the ball mill slurry to obtain a mixture B; S5, adding a binder to the mixture B and granulating it, screening it, and pressing it into a green body; S6, debinding the green body and sintering it to obtain BiVO4-based microwave dielectric ceramics.

[0011] Furthermore, the purity of the original powders of Bi2O3, La2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3 and NH4VO3 in S1 is not less than 99.9%.

[0012] Furthermore, the medium used in the primary wet ball milling in S2 and the secondary wet ball milling in S4 was anhydrous ethanol, the ball milling speed was 300 r / min, and the rotation direction was reversed every 60 minutes.

[0013] Furthermore, the pre-calcination temperature in S3 is 600-700° C. and the pre-calcination time is 2-6 hours.

[0014] Preferably, the pre-calcination temperature in S3 is 650° C. and the pre-calcination time is 4 hours.

[0015] Furthermore, the binder in S5 is a polyvinyl alcohol solution with a mass concentration of 10%, and the mass of the binder is 5-8% of the mass of the mixture B.

[0016] Furthermore, a 60-120 mesh sieve is used for screening in S5.

[0017] Furthermore, the debinding temperature in S6 is 550° C. and the time is 6 h; the sintering temperature in S6 is 740-860° C. and the time is 2 h.

[0018] Preferably, the sintering temperature in S6 is 800°C.

[0019] The beneficial effects of the present invention are: 1. The present invention precisely dopes BiVO4 with a variety of equivalent rare earth ions (La 3+ 、Nd 3+ 、Sm 3+ 、Eu 3+ and Gd 3+ ), can effectively induce and control BiVO4-based microwave dielectric ceramics [chemical formula is Bi 1-5x (La x Nd x Sm x Eu x Gd x )VO4, where 0.025≤x≤0.1], thus achieving a phase transition process in microwave dielectric ceramics while maintaining a serialized dielectric constant and also having an excellent quality factor, especially a near-zero resonant frequency temperature coefficient. In particular, when the x value is 0.055, the microwave dielectric ceramics exhibit a near-zero τ of +8.42 ppm / °C. f The value fully proves the effectiveness of regulating the phase transition of BiVO4 ceramics by multi-ion co-doping in the present invention to achieve temperature stability of the resonant frequency.

[0020] 2. The microwave dielectric ceramics prepared in this invention have a sintering temperature of 740-860°C, significantly lower than that of conventional microwave dielectric ceramics (such as BaO-TiO2 and ZrTiO4). This low-temperature sintering significantly reduces energy consumption during the sintering process, directly lowering production costs. It also extends the service life of sintering furnace components and reduces maintenance costs, aligning with the trend of green manufacturing. Furthermore, this sintering temperature enables low-temperature co-firing of dielectric ceramics and silver electrodes. By printing multiple layers of silver electrodes within dielectric ceramic devices, this allows for miniaturization of dielectric ceramic device modules, meeting the high-integration requirements of 5G / 6G communication equipment.

[0021] 3. The dielectric ceramic material Bi prepared by the present invention 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (where 0.025≤x≤0.1) has excellent microwave dielectric properties, its ε rThe value reaches 19.85~66.98, the Q×f value reaches 7904~16240 GHz, especially when x=0.055, it reaches a near-zero τ of +8.42ppm / ℃ f It has a high value and can be widely used in microwave devices such as dielectric substrates, resonators and filters, and has significant industrial application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 XRD patterns of the multi-ion co-doped BiVO4-based microwave dielectric ceramics prepared in Examples 1 to 6.

[0023] Figure 2 These are the XRD patterns and SEM images of the multi-ion co-doped BiVO4-based microwave dielectric ceramics prepared in Example 1, where a is the XRD pattern and b is the SEM pattern.

[0024] Figure 3 These are the XRD patterns and SEM images of the multi-ion co-doped BiVO4-based microwave dielectric ceramics prepared in Example 2, where a is the XRD pattern and b is the SEM pattern.

[0025] Figure 4 These are the XRD patterns and SEM images of the multi-ion co-doped BiVO4-based microwave dielectric ceramics prepared in Example 3, where a is the XRD pattern and b is the SEM pattern.

[0026] Figure 5 These are the XRD patterns and SEM images of the multi-ion co-doped BiVO4-based microwave dielectric ceramics prepared in Example 4, where a is the XRD pattern and b is the SEM pattern.

[0027] Figure 6 These are the XRD patterns and SEM images of the multi-ion co-doped BiVO4-based microwave dielectric ceramics prepared in Example 5, where a is the XRD pattern and b is the SEM pattern.

[0028] Figure 7 These are the XRD patterns and SEM images of the multi-ion co-doped BiVO4-based microwave dielectric ceramics prepared in Example 6, where a is the XRD pattern and b is the SEM pattern. DETAILED DESCRIPTION

[0029] Various exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings.

[0030] The present invention selects equivalent La 3+ 、Nd 3+ 、Sm 3+ 、Eu 3+ and Gd 3+ As Bi 3+ A series of Bi 1-5x (Lax Nd x Sm x Eu x Gd x The present invention not only opens up a new method for adjusting the temperature stability of the resonant frequency of BiVO4 ceramics, but also provides valuable design ideas for the structure-performance relationship of BiVO4-based ceramics.

[0031] Multi-ion co-doped BiVO4-based microwave dielectric ceramics Bi 1-5x (La x Nd x Sm x Eu x Gd x The specific preparation method of )VO4 (0.025≤x≤0.1) is: (1) Bi2O3, La2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3 and NH4VO3 raw powders with a purity of more than 99.9% (weight percentage) were prepared by 1-5x (La x Nd x Sm x Eu x Gd x )Weigh and proportion the ingredients of VO4 (0.025≤x≤0.1); (2) The original powder weighed in the above step is mixed and added into the ball mill for wet ball milling. The ball milling time is The milling process was carried out for 6 hours, the ball milling medium was anhydrous ethanol, the ball milling speed was 300 r / min, the rotation direction was reversed every 60 minutes, and the mixture was dried at 120°C to obtain a mixture A; (3) Pre-calcining the mixture A obtained in step (2) at 600-700°C for 2-6 hours, preferably 650°C for 4 hours, to obtain a pre-calcined powder; (4) The calcined powder obtained in step (3) was added to a ball mill for secondary wet ball milling. The ball milling time was 6 h, the ball milling medium was anhydrous ethanol, the ball milling speed was 300 r / min, the rotation was reversed every 60 min, and the mixture was dried at 120°C to obtain a mixture B. (5) Adding a binder to the mixture B obtained in step (4), wherein the binder is a polyvinyl alcohol solution with a mass concentration of 10%, and the mass of the binder is 5-8% of the mass of the mixture B, preferably 7%; granulating the mixture B after adding the binder, and passing it through a 60-120 mesh sieve to obtain a microwave dielectric ceramic powder, and pressing the microwave dielectric ceramic powder into a cylindrical green body using a powder tablet press; the green body has a diameter of 11-12 mm and a thickness of 5-6 mm; (6) The green body obtained in step (5) was debinded at 550 ° C for 6 h with a heating rate of 1.5 ° C / min, and finally sintered in an atmosphere of 740 ~ 860 ° C for 2 h, preferably 800 ° C, to obtain a multi-ion co-doped BiVO4-based microwave dielectric ceramic Bi with resonant frequency temperature stability. 1-5x (La x Nd x Sm x Eu x Gd x )VO4(0.025≤x≤ 0.1).

[0032] All the raw materials used above were purchased from the market.

[0033] The sintering temperature of microwave dielectric ceramics is the core control parameter in its preparation process, which directly determines the material's microstructure (i.e., ceramic density, grain boundaries and phase composition, etc.), dielectric properties, and industrial feasibility. In addition to changing the composition, improving the dielectric properties of microwave dielectric ceramics can also be achieved by improving the preparation process. Generally speaking, significantly improving the sintering process of microwave dielectric ceramic devices can significantly improve the performance of ceramic materials. By adjusting the sintering temperature to control the microstructure, ε can be indirectly coordinated. r , Q value, τ f The contradiction of the values. Under normal circumstances, high-density ceramic samples have the best dielectric properties, and the presence of microscopic pores will impair the dielectric properties. In the present invention, x takes the values ​​of 0.025, 0.05, 0.055, 0.057, 0.075, and 0.1, respectively, and the sintering temperatures of 740°C, 760°C, 780°C, 800°C, 820°C, 840°C, and 860°C are respectively carried out for each value of x. After testing the performance indicators of the ceramic samples at the above different sintering temperatures, it was found that when the value of x is the same, the target product Bi cannot be synthesized when the sintering temperature is lower than 740°C. 1-5x (La x Nd x Sm x Eu x Gd x )VO4. The bulk density of the ceramic sample increases with increasing temperature when sintering at temperatures between 740°C and 800°C. Above 800°C, the bulk density gradually decreases with increasing temperature. In other words, the ceramic sample sintered at 800°C in air for 2 hours achieves the highest degree of densification and exhibits the best overall microwave dielectric properties. Table 1 lists the performance indicators at various sintering temperatures.

[0034] Table 1 Performance index values ​​of microwave dielectric ceramics with different x values ​​at different sintering temperatures

[0035] Example 1: The value of x is 0.055. The above preparation method is adopted, wherein the mixture A is pre-sintered at 650℃ for 4h and the green body sintering temperature is 800℃ to obtain a multi-ion co-doped BiVO4-based microwave dielectric ceramic Bi with temperature stability of resonant frequency. 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x = 0.055).

[0036] In this embodiment 1, the microwave dielectric ceramic Bi 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x = 0.055), whose XRD pattern and SEM pattern are shown in Figure 2 After sintering at 800℃ for 2h, the diffraction peaks of the ceramic material match those of monoclinic scheelite (No. 96-901-3437) and tetragonal zircon (No. 96-901-1742), which indicates that under this sintering condition, Bi 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x = 0.055) ceramics exhibit a dual crystal structure of monoclinic scheelite and tetragonal zircon, with the two phases in similar proportions. SEM images further reveal the dense arrangement of ceramic grains, clear grain boundaries, and the absence of obvious pores, further demonstrating the high-quality sintering state of the ceramic sample. In particular, the τ f The value reaches +8.42 ppm / °C, which is close to zero, showing the remarkable effect of the present invention in achieving temperature stability of the resonant frequency.

[0037] Example 2: The value of x is 0.025. The above preparation method is adopted, wherein the mixture A is pre-sintered at 650℃ for 2h and the green body sintering temperature is 780℃ to obtain a multi-ion co-doped BiVO4-based microwave dielectric ceramic Bi with temperature stability of resonant frequency. 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x=0.025).

[0038] In this embodiment 2, the microwave dielectric ceramic Bi 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x = 0.025), whose XRD patterns and SEM images are shown in Figure 3 Parts a and b of Figure 3 The X-ray diffraction analysis shown in the figure shows that the diffraction peaks of the sample sintered at 780℃ for 2h match those of monoclinic scheelite (No. 96-901-3437) and tetragonal zircon (No. 96-901-1742), which indicates that under this sintering condition, Bi 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x=0.025) ceramics exhibit a dual crystal structure of monoclinic scheelite and tetragonal zircon, with the monoclinic scheelite phase being predominant. SEM images reveal densely packed ceramic grains, clear grain boundaries, and the absence of significant pores, demonstrating high-quality sintering of the ceramic sample and minimizing the influence of the preparation process on the ceramic's properties. 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x=0.025) ceramics τ f The value is -173.83 ppm / ℃.

[0039] Example 3: The value of x is 0.05. The above preparation method is adopted, wherein the mixture A is pre-sintered at 700℃ for 4h and the green body sintering temperature is 780℃ to obtain a multi-ion co-doped BiVO4-based microwave dielectric ceramic Bi with resonant frequency temperature stability. 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x=0.05).

[0040] In this embodiment 3, the microwave dielectric ceramic Bi 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x = 0.05), whose XRD patterns and SEM images are shown in Figure 4 Parts a and b of Figure 4 The X-ray diffraction analysis shown in the figure shows that the diffraction peaks of the sample sintered at 780℃ for 2h match those of monoclinic scheelite (No. 96-901-3437) and tetragonal zircon (No. 96-901-1742), which indicates that under this sintering condition, Bi 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x=0.05) ceramics exhibit a dual crystal structure of monoclinic scheelite and tetragonal zircon, but the monoclinic scheelite phase is still dominant. SEM images reveal the dense arrangement of ceramic grains, clear grain boundaries, and the absence of obvious pores, indicating the high-quality sintering state of the ceramic sample and minimizing the influence of the preparation process on the ceramic properties. 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x=0.05) ceramics τ f The value is -54.09 ppm / ℃.

[0041] Example 4: The value of x is 0.057. The above preparation method is adopted, wherein the mixture A is pre-sintered at 700℃ for 6h and the green body sintering temperature is 800℃ to obtain a multi-ion co-doped BiVO4-based microwave dielectric ceramic Bi with temperature stability of resonant frequency. 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x=0.057).

[0042] In this embodiment 4, the microwave dielectric ceramic Bi 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x = 0.057), whose XRD pattern and SEM pattern are shown in Figure 5 Parts a and b of Figure 5 The X-ray diffraction analysis shown in the figure shows that the diffraction peaks of the sample sintered at 800℃ for 2h match those of monoclinic scheelite (No. 96-901-3437) and tetragonal zircon (No. 96-901-1742), which indicates that under this sintering condition, Bi1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x=0.057) ceramics exhibit a dual crystal structure of monoclinic scheelite and tetragonal zircon, with the ratio of the two phases approaching x=0.055, but the tetragonal zircon phase still dominates. SEM images reveal the dense arrangement of ceramic grains, clear grain boundaries, and the absence of significant pores, demonstrating the high-quality sintering of the ceramic sample and minimizing the influence of the preparation process on the ceramic properties. 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x=0.057) ceramics τ f The value is +23.97 ppm / ℃.

[0043] Example 5: The value of x is 0.075. The above preparation method is adopted, wherein the mixture A is pre-sintered at 600℃ for 3h and the green body sintering temperature is 840℃ to obtain a multi-ion co-doped BiVO4-based microwave dielectric ceramic Bi with temperature stability of resonant frequency. 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x=0.075).

[0044] In this embodiment 5, the microwave dielectric ceramic Bi 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x = 0.075), whose XRD pattern and SEM pattern are shown in Figure 6 Parts a and b of Figure 6 The X-ray diffraction analysis shown in the figure shows that the sample sintered at 840°C for 2 hours only exhibits diffraction peaks corresponding to tetragonal zircon (numbers 96-901-1742), with no other phases detected. This indicates that at this sintering temperature, the material forms a single phase of cubic tetragonal zircon. The SEM image reveals the dense arrangement of ceramic grains, clear grain boundaries, and the absence of significant pores, demonstrating the high-quality sintering state of the ceramic sample and minimizing the influence of the preparation process on the ceramic properties. 1-5x (La x Nd x Smx Eu x Gd x )VO4 (x=0.075) ceramics τ f The value is +158.34 ppm / ℃.

[0045] Example 6: The value of x is 0.1. The above preparation method is adopted, wherein the mixture A is pre-sintered at 600℃ for 5h and the green body sintering temperature is 840℃ to obtain a multi-ion co-doped BiVO4-based microwave dielectric ceramic Bi with temperature stability of resonant frequency. 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x=0.1).

[0046] In this embodiment 6, a microwave dielectric ceramic Bi 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x = 0.1), whose XRD pattern and SEM pattern are shown in Figure 7 Parts a and b of Figure 7 The X-ray diffraction analysis shown in the figure shows that the sample sintered at 840°C for 2 hours only exhibits diffraction peaks corresponding to tetragonal zircon (numbers 96-901-1742), with no other phases detected. This indicates that at this sintering temperature, the material forms a single phase of cubic tetragonal zircon. The SEM image reveals the dense arrangement of ceramic grains, clear grain boundaries, and the absence of significant pores, demonstrating the high-quality sintering state of the ceramic sample and minimizing the influence of the preparation process on the ceramic properties. 1-5x (La x Nd x Sm x Eu x Gd x )VO4 (x = 0.1) ceramics τ f The value is +151.81 ppm / ℃.

[0047] The XRD patterns of the multi-ion co-doped BiVO4-based microwave dielectric ceramics prepared in Examples 1 to 6 are shown in FIG. Figure 1 .

[0048] The microwave dielectric properties of the multi-ion co-doped BiVO4-based microwave dielectric ceramics prepared in Examples 1 to 6 above were tested, and the results are shown in Table 2.

[0049] Table 2 Bi 1-5x(La x Nd x Sm x Eu x Gd x )Microwave Dielectric Properties of VO4 Microwave Dielectric Ceramics

[0050] It can be seen from Table 2 that the multi-ion co-doped BiVO4-based microwave dielectric ceramic materials ε r The values ​​show a series range of 19.85~66.98, and the Q×f value reaches 7904~16240 GHz, especially when x=0.055, it reaches a near-zero τ of +8.42ppm / ℃. f The ceramic material prepared in Example 1 successfully achieved a near-zero τ f In contrast, the ceramic materials prepared in Examples 2 to 6 showed either negative or positive non-zero τ f The difference in these results fully demonstrates the feasibility and effectiveness of regulating the phase transition of BiVO4 ceramics by multi-ion co-doping to achieve its temperature stability in the present invention.

[0051] The present invention precisely dopes BiVO4 with multiple equivalent rare earth ions (La 3+ 、Nd 3+ 、Sm 3+ 、Eu 3+ and Gd 3+ ), can effectively induce and control BiVO4-based microwave dielectric ceramics [chemical formula is Bi 1-5x (La x Nd x Sm x Eu x Gd x )VO4, where 0.025≤x≤0.1]. When the x value is 0.025~0.057, the XRD pattern of the obtained ceramic sample is completely consistent with the common diffraction peaks of the monoclinic scheelite phase BiVO4 (number 96-901-3437) and the tetragonal zircon phase (number 96-901-1742), indicating that Bi 1-5x (La x Nd x Sm x Eu x Gd x)VO4 ceramics present a dual-phase coexistence of monoclinic scheelite and tetragonal zircon, and as the x value gradually increases within this range, the proportion of scheelite phase gradually decreases and the proportion of zircon phase gradually increases; when the x value further increases to 0.075~0.1, the scheelite phase completely disappears and the ceramics completely transform into a zircon phase structure. At this time, Bi 1-5x (La x Nd x Sm x Eu x Gd x )VO4 ceramics are tetragonal zircon single phase. Through the above multi-ion solid solution phase transition strategy, Bi 1-5x (La x Nd x Sm x Eu x Gd x ) VO4 ceramics τ f From negative to near zero and finally to positive. Especially when the x value is 0.055, the ceramic sample shows a near-zero τ of +8.42 ppm / ℃ f The value fully proves the effectiveness of regulating the phase transition of BiVO4 ceramics by multi-ion co-doping in the present invention to achieve temperature stability of the resonant frequency.

[0052] The microwave dielectric ceramics prepared in this invention have a sintering temperature of 740-860°C, significantly lower than the sintering temperatures of conventional microwave dielectric ceramics (such as BaO-TiO2 and ZrTiO4) (typically 1200-1400°C). Therefore, this low-temperature sintering significantly reduces energy consumption during the sintering process, directly lowering production costs. It also extends the service life of sintering furnace components (such as heaters, charging saggers, push plates, and sintering chambers), reducing maintenance costs and aligning with the trend toward green manufacturing. Most importantly, this sintering temperature is below the melting point of metallic silver, a common electrode in electronic ceramic devices. Therefore, this low-temperature sintering method enables low-temperature co-firing of dielectric ceramics and silver electrodes. By printing multiple layers of silver electrodes within dielectric ceramic devices, this allows for miniaturization of device modules, meeting the high-integration requirements of 5G / 6G communication equipment. Since the present invention can realize multi-layer printing of silver electrodes inside dielectric ceramic devices, the preparation of the microwave dielectric ceramics of the present invention is not limited to the dry pressing process using a powder tablet press in the above-mentioned preparation method, but can also be formed using a casting process. During the casting process, multi-layer electrodes can be buried between the ceramic layers inside the product according to the design requirements of the product parameter indicators. The ceramic and the electrode can be co-fired once to become a microwave dielectric ceramic device, thereby realizing the miniaturization of the device module and meeting the high integration requirements of 5G / 6G communication equipment.

[0053] In summary, the strategy designed by the present invention to adjust the BiVO4 phase transition by multi-ion co-doping to achieve temperature stability is feasible, which not only provides a basis for designing a near-zero τ f This study provides a new method for the development of microwave dielectric ceramics and has certain guiding significance for the development of advanced microwave materials with better performance and higher reliability.

[0054] The embodiments described above are merely descriptions of preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Without departing from the spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by persons skilled in the art should fall within the scope of protection defined by the claims of the present invention.

[0055] In addition, for numerical ranges in the present invention, it is understood that each intervening value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between any stated value or stated range, and any other stated value or intervening value in the stated range, is also included in the present invention. The upper and lower limits of these smaller ranges may independently be included or excluded in the range.

[0056] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0057] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention pertains. Although preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein can also be used in the practice or testing of the present invention.

Claims

1. A multi-ion co-doped BiVO4-based microwave dielectric ceramic, characterized in that: Its chemical formula is Bi 1-5x (La x Nd x Sm x Eu x Gd x )VO4, where 0.025≤x≤0.

1.

2. The multi-ion co-doped BiVO4-based microwave dielectric ceramic according to claim 1, characterized in that: x=0.055。 3. The method for preparing multi-ion co-doped BiVO4-based microwave dielectric ceramics according to claim 1 or 2, characterized in that: The following steps are involved: S1, the original powders of Bi2O3, La2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3 and NH4VO3 were prepared according to Bi 1-5x (La x Nd x Sm x Eu x Gd x ) Weighing and mixing the components of VO4; S2, mixing the original powders weighed in S1 and performing wet ball milling, and drying the ball mill slurry to obtain a mixture A; S3, pre-calcining the mixture A to obtain a pre-calcined powder; S4, performing a secondary wet ball milling on the pre-calcined powder obtained in S3, and drying the ball mill slurry to obtain a mixture B; S5, adding a binder to the mixture B and granulating it, screening it, and pressing it into a green body; S6, debinding the green body and sintering it to obtain BiVO4-based microwave dielectric ceramics.

4. The method for preparing multi-ion co-doped BiVO4-based microwave dielectric ceramics according to claim 3, characterized in that: The purity of the original powders of Bi2O3, La2O3, Nd2O3, Sm2O3, Eu2O3, Gd2O3 and NH4VO3 in S1 is not less than 99.9%.

5. The method for preparing multi-ion co-doped BiVO4-based microwave dielectric ceramics according to claim 3, characterized in that: The medium used in the primary wet ball milling in S2 and the secondary wet ball milling in S4 was anhydrous ethanol, the ball milling speed was 300 r / min, and the rotation was reversed every 60 minutes.

6. The method for preparing multi-ion co-doped BiVO4-based microwave dielectric ceramics according to claim 3, characterized in that: The pre-calcination temperature in S3 is 600-700° C. and the pre-calcination time is 2-6 hours.

7. The method for preparing multi-ion co-doped BiVO4-based microwave dielectric ceramics according to claim 6, characterized in that: The pre-calcination temperature in S3 is 650° C. and the pre-calcination time is 4 hours.

8. The method for preparing multi-ion co-doped BiVO4-based microwave dielectric ceramics according to claim 3, characterized in that: The binder in S5 is a polyvinyl alcohol solution with a mass concentration of 10%, and the mass of the binder is 5-8% of the mass of the mixture B.

9. The method for preparing multi-ion co-doped BiVO4-based microwave dielectric ceramics according to claim 3, characterized in that: The debinding temperature in S6 is 550° C. and the time is 6 hours; the sintering temperature in S6 is 740-860° C. and the time is 2 hours.

10. The method for preparing multi-ion co-doped BiVO4-based microwave dielectric ceramics according to claim 9, characterized in that: The sintering temperature in S6 is 800°C.

Citation Information

Patent Citations

  • Ultralow-temperature-sintering microwave dielectric ceramic NaBi3V2O10

    CN106045509A

  • Vanadium indium co-doped niobate bismuth rubidium piezoceramic material and preparation method thereof

    CN108997011A

  • Preparation method and application of rare earth molybdate ceramic material synthesized by molten salt method

    CN117902898A

  • Vanadium-based zircon microwave dielectric ceramic and preparation method thereof

    CN119430928A

  • Piezoelectric ceramic composition, its production method, piezoelectric element, and dielectric element

    JP2004244299A